Project citizen model to develop student's pro-social awareness - Romlah, Oom Yomi; Syobar, Khaerul (Universitas Negeri Yogyakarta, 2021)
Students' learning activities cannot be separated from various factors. The purpose of this study was to determine how project citizen model developed students' pro-social awareness. This study was motivated by diminishing pro- social awareness among students. This study was conducted qualitatively by using case study. The results showed that through project citizen model, students' pro-social awareness could develop. Besides, project citizen model could help students think critically about social reality. This study recommended to maximize the use of project citizen as a learning model that could develop various potencies of students.